Pengembangan Media Video Pembelajaran Berbasis Budaya Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD: Development of Culture-Based Learning Video Media to Improve Learning Outcomes of Grade V Elementary School Students - Andrean Jaya; Mustafa Habib; Azri Ranuwaldy Sugma (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Teachers use lecture methods, textbooks, and LKS media to direct student learning. However, media use is still not optimal and diverse, so learning becomes repetitive and can cause student boredom. This study uses a research and development (R&D) approach. The approach model used is the ADDIE model (Analyze, Design, Development, Implementation, evaluation). Fifth-grade students at SDN 050659 Stabat became the subjects of the study. Data collection techniques used in this study include questionnaires, interviews, and documentation. Validity questionnaires collected from media and material experts were used to analyze research findings. Questionnaire criteria from teachers and students were used to determine practicality criteria. The product's validity feasibility is at a very valid qualification. The assessment of media experts is at a qualification of 91%, while material experts are at a qualification of 92%. Individual trial data showed a success rate of 91%; there was a 90% success rate qualified as very valid in the teacher response results, a 90% success stage qualified as very valid in small group trials, and a 90% success stage qualified as very valid in large group trials. The increase in student learning outcomes is shown by the N-Gain score of 80.36 in the practical category, which indicates that the product is feasible to apply in the learning process. According to research findings, using culture-based learning video media can help students become more active and productive learners.